Computational intelligence for medical internet of things (MIoT) applications machine intelligence applications for IoT in healthcare - Maleh, Yassine, 1987-; Abd El-Latif, Ahmed A., 1984-; Curran, Kevin, 1969-; Siarry, Patrick (Advances in ubiquitous sensing applications for healthcare, 2023)
Computational Intelligence for Medical Internet of Things (MIoT) Applications: Machine Intelligence Applications for IoT in Healthcare explores machine intelligence techniques necessary for effective MIoT research and practice, taking a practical approach for practitioners and students entering the field. This book investigates advanced concepts and applications in the MIoT field, guiding readers through emerging developments and future trends. A wide range of international authors guide readers through advanced concepts, including deep learning, neural network, and big data analytic approaches for the classification, indexing, retrieval, analysis, and inferencing of healthcare data.